Saccharomyces cerevisiae Laryngitis and Oral Lesions in a Patient with Laryngeal Carcinoma - Jumanah N. Algazaq; Kevan Akrami; Fernando Martinez; Allen McCutchan; Ajay R. Bharti (Case Reports in Infectious Diseases)
Saccharomyces cerevisiae is increasingly being promoted as a nutritional supplement by health food enthusiasts and is also recommended as prophylaxis against antibiotic-associated diarrhea. However, severe opportunistic infections due to S. cerevisiae have been reported in patients with chronic disease, cancer, and immunosuppression. Fungemia, endocarditis, pneumonia, peritonitis, urinary tract infections, skin infections, and esophagitis have been described. It is important to consider infections due to S. cerevisiae in appropriate clinical settings. Here, we describe the first case of S. cerevisiae laryngitis in a patient with a history of laryngeal carcinoma who also had oral lesions.